Low Nitrogen Priming Enhances Photosynthesis Adaptation to Water-Deficit Stress in Winter Wheat (Triticum aestivum L.) Seedlings - Gao, Jingwen; Luo, Qiuci; Sun, Chuanjiao; Hu, Hang; Wang, Feng; Tian, Zhongwei; Jiang, Dong; Cao, Weixing; Dai, Tingbo (Frontiers in Plant Science, 2019)
Drought is among the main environmental stressors that reduces wheat production. Nitrogen (N) availability affects plant adaptation to abiotic stress, but the effect of low N (LN) on drought tolerance is unclear. To identify the effect of LN priming on drought tolerance in wheat seedlings, we primed cultivar Yangmai158 with 0.25 mM N for 7 days, and then added 20% polyethylene glycol 6000 as a drought treatment for 5 days. The net photosynthetic rate, plant biomass, and plant growth rate were significantly reduced under drought conditions; such decreases were less severe in LN-primed (LND) plants than non-primed (CKD) plants. The leaf relative water content (LRWC) decreased under drought conditions, which in turn led to a reduced transpiration rate, stomatal conductance, and intercellular CO2 concentration, causing a stomatal limitation on photosynthesis. LN priming also enhanced root growth, resulting in a higher LRWC and less stomatal limitation in LND plants than CKD plants. PSII quantum efficiency, photochemical quenching, and maximum PSII quantum efficiency were reduced under drought conditions, indicating photoinhibition. However, LN priming increased the electron flux to photorespiration and the Mehler pathway, reducing photoinhibition. In conclusion, LN priming improved the leaf water status and increased alternative electron flux to attenuate photoinhibition, thus alleviating the inhibition of photosynthesis and growth due to drought.